Femoral resection accuracy and precision in manual caliper‐verified kinematic alignment total knee arthroplasty - David Forrest Scott; Emma N. Horton (Journal of Experimental Orthopaedics, 2025)
Abstract Introduction The accuracy and precision of bone resections in total knee arthroplasty (TKA) are essential to avoid poor implant positioning, which can lead to component wear, pain, and instability, reducing patient satisfaction and implant survivorship. Technology‐assisted TKA techniques aim to improve accuracy but come with added costs, increased operative time, and varying success in clinical outcomes. Caliper‐verified kinematic alignment (KA) attempts to restore the joint line by precisely measuring resections to equal implant thickness. We evaluated the accuracy and precision of caliper‐verified KA‐TKA performed with manual instruments. We hypothesised that this technique would achieve high accuracy and precision, with an average absolute difference between actual and target distal and posterior femoral resection measurements of ≤ 0.5 mm. Methods 385 consecutive patients underwent primary unrestricted caliper‐verified KA‐TKA with manual instrumentation. The thickness of the distal medial (DM), distal lateral (DL), posterior medial (PM) and posterior lateral (PL) femoral condyle resections were measured with a caliper and compared to a target determined by the degree of cartilage loss, saw blade kerf, and femoral component thickness. Results The mean differences between the resected and target thicknesses for DM, DL, PM and PL femoral resections were 0.1 ± 0.2 mm, 0.1 ± 0.3 mm, 0.3 ± 0.5 mm and 0.2 ± 0.4 mm, respectively (mean ± std. dev.). Most femoral resections were within 0.5 mm of the target—97.7%, 94.5%, 85.7% and 89.4% of DM, DL, PM and PL resections, respectively. Conclusion Manual caliper‐verified KA‐TKA achieved highly accurate and precise femoral resections with absolute differences from target that averaged 0.175 mm. This simple, logical, efficient, and reproducible surgical technique may be an option for surgeons contemplating the use of technology‐assisted options, such as patient‐specific instrumentation or robotic arm‐assisted TKA, and surgeons without access to such technologies. Level of Evidence Level II.